2012
DOI: 10.3109/17435390.2012.736547
|View full text |Cite
|
Sign up to set email alerts
|

Generation of toxic degradation products by sonication of Pluronic® dispersants: implications for nanotoxicity testing

Abstract: Poloxamers (known by the trade name Pluronic®) are triblock copolymer surfactants that contain two polyethylene glycol blocks and one polypropylene glycol block of various sizes. Poloxamers are widely used as nanoparticle dispersants for nanotoxicity studies wherein nanoparticles are sonicated with a dispersant to prepare suspensions. It is known that poloxamers can be degraded during sonication and that reactive oxygen species contribute to the degradation process. However, the possibility that poloxamer degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 26 publications
3
76
0
1
Order By: Relevance
“…suspension after the preparation process. Recently, Wang et al (2013) reported that surfactants such us Pluronic F127 and Pluronic F68 can become highly toxic to cells due to degradation, during the sonication process. Another study has demonstrated that Pluronic F127 in concentrations as low as 0.01% can induce cell apoptosis on mouse cortical neurons, while the presence of MWCNTs can reduce toxicity (Bardi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…suspension after the preparation process. Recently, Wang et al (2013) reported that surfactants such us Pluronic F127 and Pluronic F68 can become highly toxic to cells due to degradation, during the sonication process. Another study has demonstrated that Pluronic F127 in concentrations as low as 0.01% can induce cell apoptosis on mouse cortical neurons, while the presence of MWCNTs can reduce toxicity (Bardi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The bath sonication, centrifugation and dialysis procedures described in our previous work (Wang et al, 2013b) were used with slight modifications to disperse MWNT or SWNT powders in an aqueous 0.2mM PF108 solution. In general, 10mL of 0.2mM PF108 solution was added to a glass vial containing 10 mg pMWNT, cMWNT, pSWNT, or cSWNT powder and sonicated for 1 h at 37 kHz and 120W.…”
Section: Methodsmentioning
confidence: 99%
“…The physical and chemical properties of these CNT preparations have been previously characterized in addition to their effects on cultured mammalian cells (Wang et al, 2011, 2013b). All the CNTs in PF108 suspensions studied here accumulated in zebrafish embryos in a concentration-dependent manner but only the carboxylated SWNTs were toxic, similar to results found with cultured mammalian cells (Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…4.13 Sonication control with media and organic chemicals/coatings: The purpose of this control is to investigate possible changes to media constituents or toxicological properties of organic chemicals from sonication (19). This control can be tested by adding the test media and any organic chemicals in the test media (e.g., cholesterol), dispersants, or coatings to the container used to sonicate samples, sonicating this sample using the same conditions as those that will be used to disperse the ENMs, and then assessing if this solution would impact the ecotoxicological endpoint being studied.…”
Section: Nutrient Depletion Controlmentioning
confidence: 99%